An alternative to estimate the atmospheric carbon sequestration by Bambusa vulgaris var. vulgaris Schrad. ex J.C. Wendl. - Alicia Mercadet; José A. Bravo; Hilda Quesada; Manuel Valle; Dulce Almonte (Biotecnología Vegetal, 2011)
The estimation of atmospheric carbon sequestration by a woody plant has two alternatives for implementation: by identifying the average annual increase in volume or by determining the appropriate method for calculating the volume stand. The aim of this work was to obtain a reliable and simple method for estimating the carbon in plants and culms of bamboo (Bambusa vulgaris var. vulgaris) existing in a territory. Single samples were taken without replacement in different areas and each culm was measured in total length, outside diameter and wall thickness every two meters from the base to the segment in the upper left to present an interior cavity identifiable, in which the remaining length to the top was measured. Graphical analyses were conducted with the data collected of trends in relations between the variables considered along the culm. By regression analysis with different models and the use of determination coefficient (R2) as an adjustment indicator, we selected those that best allow estimating the solid volume of the culm. After obtaining the calibration models and their results, we prepared a spreadsheet that facilitates to take down the values of the different variables by culm and scion as well as the characterization of the scion average culm. The results are a first attempt to develop a method for estimating the carbon sequestered by the bamboo culm at both as scion and territory to include this element among the criteria for the management plans of this non-wood forest resource.